SPORTS SPIRITUALITY IN RESACRALIZATION OF POLITICAL PHENOMENON - I. L. Biryukov (Современная наука и инновации, 2022)
The author examines the relationship between politics and sports in the aspect of political theology. The relevance of the topic of the article lies in the need to understand the relationship between politics and sports in modern conditions. As the goal of the article, the author sets the search for an approach to the problem of the relationship between religious, political and spiritual on the basis of sports activity. In the first part of the article, the author conducted the necessary analysis of the concepts of spirituality as comprehension of God in a religious aspect, and in the second part he focused on defining the concept of spirituality in sports politics. It is concluded that politics should not be seen as the only determining factor in sports spirituality. The religious perspective of the resacralization of the political field of sport is no less important and essential in modern Russian society. As a result, the functions of sports spirituality in sports policy were revealed and the applied aspect of this direction was indicated.